Dynamics of price competition in Italian pharmaceutical off-patent market - Perna, Serena; Cangini, Agnese; Marini, Roberto; Guerrizio, Maria Alessandra; Da Cas, Roberto; Traversa, Giuseppe; Trotta, Francesco (Frontiers in Medicine, 2022)
Introduction The aim of the study was to evaluate, in a regulated generics market, the effect of the number of manufacturers of generic drugs on the amplitude of off-patent products price reduction and the price evolution of originators and generics after the patent expiry of pharmaceuticals dispensed by community pharmacies and reimbursed by the Italian National Health Service (INHS). Methods The AIFA “transparency list” was utilized to select unbranded and branded off-patent drug dispensed by community pharmacies and reimbursed by the Italian National Health Service between 2012 and 2018. The unbranded drug entry in the transparency list database was considered as a proxy of its patent expiry. Results A total of 42 different active ingredients were included in the analysis. The relative price per dose at time t of unbranded and branded drugs, considering as common denominator the price per dose a year before the patent expiry, (t-1) decreased with the increase of unbranded manufacturers. At the time of the patent expiry, the price of unbranded drugs was almost 50% less than that of branded drugs at t-1 and the price of branded drugs started to decrease before the first unbranded entry. Conclusion An inverse relation between the number of generic drug entrants and the price of generics and originators was detected. The patent expiry determines a price decline, more concentrated in the first year of patent expiry.